2023
DOI: 10.1001/jamanetworkopen.2023.9501
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence of Gout Among US Asian Adults, 2011-2018

Abstract: ImportanceGout disparities among Black individuals in the US have recently been explained by socioclinical factors; however, no information is available among Asian individuals living in Western countries, despite their disproportionately worsening metabolic health.ObjectiveTo determine the prevalence of gout and serum urate concentrations according to race and ethnicity and to explore the association of social determinants of health and clinical factors.Design, Setting, and ParticipantsThis is a population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…One study reported that Asian Americans had a slightly lower prevalence of gout than American White, but their prevalence of gout was doubled over 6 years and became even higher than that of American White, indicating that both genetic and environmental factors play roles in the development of gout. 42 Future studies examining the incidence rate of gout according to racial/ethnic origin in the UK could help to identify risk factors and their interaction on the secular trend of gout.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that Asian Americans had a slightly lower prevalence of gout than American White, but their prevalence of gout was doubled over 6 years and became even higher than that of American White, indicating that both genetic and environmental factors play roles in the development of gout. 42 Future studies examining the incidence rate of gout according to racial/ethnic origin in the UK could help to identify risk factors and their interaction on the secular trend of gout.…”
Section: Discussionmentioning
confidence: 99%
“…Because two-thirds of the Asian adolescents in our sample were US born, we speculate that their higher cardiometabolic risk was dually influenced by genetics and by epigenetic changes due to lifestyle influences. This dual influence provides more clarity on the racial disparity of Asian American adults for conditions such as gout which has doubled in prevalence from 2011 to 2018 [26]. Studies have found individuals with Asian heritages to be genetically disposed to elevated uric acid levels and when combined with Western diets rich in purines and sedentary lifestyles; thus, the risk of complications such as hyperuricemia, gout, and cardiovascular risk are further elevated in Asian Americans [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These factors affect serum urate levels and may be confounders of the associations studied here. Race and ethnicity were included because previous studies reported higher rates of gout in Black and Asian individuals compared with White individuals …”
Section: Methodsmentioning
confidence: 99%
“…Gout affects more than 12 million adults in the US . Acute gout is typically episodic and associated with severe pain, reduced quality of life, and a transient increase in major cardiovascular and venous thrombotic events .…”
Section: Introductionmentioning
confidence: 99%

Serum Urate and Recurrent Gout

McCormick,
Yokose,
Challener
et al. 2024
JAMA
Self Cite